Hubungan Pola Asuh Orang Tua terhadap Pengambilan Keputusan pada Remaja Akhir - Febrianti Nurul Adha; Mustaqim Setyo Ariyanto; Fildzah Malahati (EduInovasi: Journal of Basic Educational Studies, 2026)
The study aims to investigate the correlation between parenting patterns and decision-making processes in late adolescence, this study adopted a quantitative methodology with a correlational design, involving 100 individuals of late adolescents as subjects. The measurement instrument consists of a parenting pattern scale that evaluates the dimensions of control, independence expectations, communication, and support, as well as a decision-making scale that measures self-efficacy, execution ability, social interaction, and adaptive capacity. Evaluation of the normality and linearity of the data showed that the data met the criteria for the application of parametric statistical analysis. Pearson's correlation analysis revealed a robust and meaningful positive association between parenting patterns and late adolescent decision-making (r = 0.747; p = 0.000). These findings imply that the improvement in the quality of parenting patterns correlates with an increase in adolescents' competence in carrying out autonomous decision-making. This study confirms the significance of supportive parenting patterns in facilitating the development.